2008
DOI: 10.1007/s10533-007-9172-5
|View full text |Cite
|
Sign up to set email alerts
|

Rhizogenic Fe–C redox cycling: a hypothetical biogeochemical mechanism that drives crustal weathering in upland soils

Abstract: Field-scale observations of two upland soils derived from contrasting granite and basalt bedrocks are presented to hypothesize that redox activity of rhizospheres exerts substantial effects on mineral dissolution and colloidal translocation in many upland soils. Rhizospheres are redox-active microsites and in the absence of O 2 , oxidation of rhizodeposits can be coupled by reduction of redoxactive species such as Fe, a biogenic reduction that leads to Fe translocation and oxidation, accompanied by substantial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 53 publications
0
75
0
Order By: Relevance
“…Aside from a few exceptions (Andersen et al 1998;van der Lee et al 1999;von Fischer and Hedin 2002;Fimmen et al 2008), the spatial and temporal dynamics of anaerobic microsites in upland soils, the factors controlling their formation and persistence, and their impact on soil C cycling have not been studied in great detail.…”
Section: Anaerobic Microsites and Their Impact On Om Mineralization Imentioning
confidence: 99%
See 2 more Smart Citations
“…Aside from a few exceptions (Andersen et al 1998;van der Lee et al 1999;von Fischer and Hedin 2002;Fimmen et al 2008), the spatial and temporal dynamics of anaerobic microsites in upland soils, the factors controlling their formation and persistence, and their impact on soil C cycling have not been studied in great detail.…”
Section: Anaerobic Microsites and Their Impact On Om Mineralization Imentioning
confidence: 99%
“…If oxygen supply (via diffusion) in the soil matrix is slower than its consumption (via microbial respiration), the interior of structural units (aggregates or peds) becomes oxygen depleted relative to the exterior (macropores) (as seen in Sexstone et al 1985), leading to gradients in redox potential (Zausig et al 1993). If these gradients persist, frequently promoted by seasonal water saturation (Jacobs et al 2002) or a continuous supply of root C (Richter et al 2007;Fimmen et al 2008;Hong et al 2010), they lead to the differentiation of redoximorphic features.…”
Section: Formation Of Anaerobic Microsites In Upland Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, manganese (Mn) reduction may also contribute to decomposition because Mn(IV) is a strong anaerobic oxidant, and Mn reduction may support Fe(III)-reducing bacteria (many of which reduce Mn) when redox conditions do not favor Fe(III) reduction (Lovley et al 2004). In Luquillo soils, Fe-oxides are far more abundant than Mn-oxides (Table 1) surfaces (King and Garey 1999, Nevin and Lovley 2002, Fimmen et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Fe reduction can influence colloidal mobilization physically via dissolution of particles or chemically through changes in pH and corresponding particle surface charges (Thompson et al, 2006a). Fimmen et al (2008) and Grybos et al (2009) have suggested that organic matter is likely to disperse during Fe-C redox cycles, although they do not provide direct evidence of organic colloids.…”
Section: Introductionmentioning
confidence: 99%